The Time Component of Hand Drawing (TEST XY. Critical review of studies on the representation of architecture and use of the image in science and art, 2023)
Much has been written about the differences (fundamental and not) between the drawing created with hand tools and the one generated thanks to the use of digital technology. The present investigation is based on the hypothesis that defends the relevance of considering temporality in any analysis of the process involved in drawing. Thus, and thanks to the series of critical positions that we develop and that are a consequence of the different approaches that the temporal parameter enables, we propose a new and fertile hand drawing analysis strategy. The temporal component of manual drawing is precisely the one that best allows us to critically compare it. The process (creation), the result (document) and the interpretation of the drawing will be concepts that we will redefine thanks to the relationship with time and that will allow us to articulate the discourse, first, and the strategy, later, of the construction of a contemporary classification (in relation to the digital world) of manual drawing. The very tension of the lines on the paper (Fraser, Henmi 1994: 163), as well as their verbalized perception (Prinz 1991: 20) will be put in relation to that foreign country (Markus, Cameron 2002: 120) that the time different from the current one to better explain the multiple meanings contained in the graphic signifier (fig. 1). The conclusions of the research will thus underline the limitations of the new technologies applied to drawing while allowing to illuminate the reasons why, we believe, the construction of images thanks to the combination of symbols (signifiers, spots, colors, lines ...) that we call drawing is an inherent part of the very essence of the human race and its social relationship and with the environment.
Keywords: digital drawing; hand drawing; temporality